ΔF659 and F659S substitutions at the HS1 of FKS2 gene, along with E655A and W715L upstream and downstream substitutions, correlate with high ibrexafungerp MICs against Candidaglabrata. (August 2022) - Mesquida, Aina; Díaz-García, Judith; Sánchez-Carrillo, Carlos; Martín-Rabadán, Pablo; Alcalá, Luis; Muñoz, Patricia; Escribano, Pilar; Guinea, Jesús
Abstract: Objectives: Ibrexafungerp is a new inhibitor of Candida spp glucan synthase. We previously set the ibrexafungerp wild-type upper limit (wtUL) against Candida glabrata . We here assessed which FKS2 gene substitutions confer an ibrexafungerp non-wild-type phenotype in C. glabrata isolates. Methods: We studied a set of C. glabrata ( n  = 34) isolates showing resistance to micafungin and anidulafungin ( n  = 28) or only to anidulafungin ( n  = 6) and harbouring 10 different FKS2 gene substitutions. Antifungal susceptibility to ibrexafungerp was tested according to European Committee on Antimicrobial Susceptibility Testing (EUCAST) E.Def 7.3.2 procedure and isolates were considered ibrexafungerp non-wild type according to the statistical wtUL (minimum inhibitory concentration [MIC] ≥2) or visual wtUL (MIC ≥4). Results: Ibrexafungerp MICs against the isolates ranged from 0.06 to 4 mg/L. Four FKS2 gene substitutions (ΔF659, F659S, E655A, and W715L) were exclusively found in isolates showing an ibrexafungerp MIC above the statistical wtUL (≥2 mg/L) whereas isolates harbouring other substitutions were found to be ibrexafungerp wild type. The use of the visual wtUL (MIC ≥4 mg/L) bisected the population of isolates harbouring such substitutions. Discussion: C. glabrata isolates showing an ibrexafungerp MIC ≥2 mg/L may be considered non-wild type and are prone to harbour ΔF659, F659S, E655A, and W715L substitutions at the FKS2 gene. It is worth noting that substitutions ΔF659 and F659S were located at the beginning of the HS1 of FKS2 gene of C. glabrata . The role of other substitutions on conferring a non-wild-type phenotype to ibrexafungerp is not well elucidated. Graphical abstract: Image 1